"Oh God, Please Save Us from War": AN Ethography Study of Impact of War on Health Among Syrian Children Refuges in Lebanon and Their Experience Living with Health Problems - Zulkhairul Naim Bin Sidek Ahmad; Burhanudin Busu (Asian Social Work Journal, 2019)
In nearly six years of armed conflict, more than 250,000 Syrians have lost their lives and there were over 1 million Syrian refugees who had been registered in Lebanon in 2016. It has been reported that exposure to war causes injury, illness and breakdown in the health care structures especially to children. This paper attempts to evaluate the impact of war on health in children and to explore their experience living with health problems. A qualitative data from semi structured interview was conducted among mothers in refugee camp in Bekaa Valley, Lebanon Participants were purposefully sampled and asked to share their impact on war to health of their children. All interviews were written manually and analysed thematically. Ten participants were involved in this study. There were three main themes were identified, each of which led to health risks for the children; antepartum, intrapartum and postpartum. There was variety of health problems reported ranging from neurological, musculoskeletal disorder to ocular problems. The experience living with health problems were understood through construction of three thematic categories emerged; psychological burden, disruption of daily living and economic effect. In additional, the participants also highlighted the intergenerational impact of war on health predominantly mental disorder, congenital abnormalities, infectious disease and complication in pregnancy. In general, this paper provides an important understanding of impact of wars on health among vulnerable group which is children. The effects of wars on health and health care services are substantial. All these issues should be explored more to ensure the children received adequate health care. The results generated form this study can inspire new collaboration with many authorities in the design and implementation intervention to improve health status in war zone